Perceived Academic Social Influence from Parents, Peers, and Teachers Across Gender Groups: Scale Development - Walker, Soung Hwa; Walker, Deron (Asian Journal of Contemporary Education, 2022)
This research examines psychometric properties of the 10-item Perceived Academic Social Influence Scale (PASIS) across gender groups with samples from Finland and Taiwan (Total N = 4727, 50.2% female adolescents). Results of composite scores, factor loadings, item-total correlations, and values of square root of Average Variance Extracted (AVE) confirmed strong reliability and validity of the scale. A Multi-Group Confirmatory Factor Analysis (MGCFA) revealed that measurement was equivalent at the level of scalar invariance across gender groups. Among three subcomponents of PASIS, latent mean score of teacher factor turned out to be higher than peer and parent factors regarding math achievement for female and male adolescents from both countries. Findings indicate that the PASIS is a reliable and valid measure to assess the perceptions of academic social influence for math learning, which can be utilized in different cultural contexts.